An Unusual Case of Drowning (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Drowning remains a significant cause of accidental death in young children. The site of drowning varies among the communities and is influenced by cultural and geographic factors, including the availability of particular water sources. An open shallow drain with a small collection of water let off from the bathroom turned fatal to a young toddler. Only partial submersion of face was present and had led to death characterised by the absence of pathognomonic drowning signs. This paper demonstrates specific issues that may arise in such cases. As this is a new hazard in home environment, precautions should be recommended by the forensic pathologists and awareness should be created among the public that even partial submersion in a shallow collection of water can result in fatal drowning.
Keywords: Unusual; Drowning Types; Mechanism; Autopsy